A Labour Useful to Students: Contrasting Perspectives on Teaching Translation Studies - Harry Aveling (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
Translation Pedagogy is one of the most under-developed fields of Translation Studies. This paper will provide an introduction to three different approaches to the teaching of Translation: the Classical European, the “transmissionist” approach and the contemporary “social constructivist” approach. The paper will show how the relationship between teacher and student varies in each of these models